Palladium‐Catalyzed Pyridine‐Directed Regioselective Oxidative C–H Acylation of Carbazoles by Using Aldehydes as the Acyl Source. Issue 2 (19th December 2016) - Maiti, Subhadip; Burgula, Laxminarayana; Chakraborti, Gargi; Dash, Jyotirmayee
Abstract : We herein report a highly regioselective reaction for the palladium‐catalyzed oxidative acylation of carbazole derivatives with various aromatic and aliphatic aldehydes as the acyl source. The carbazole derivatives are N ‐protected with an easily removable pyridine moiety, which directs the Pd‐catalyzed ortho acylation to occur at the C‐1 and C‐8 positions. The reactions of dibromo‐ and diiodo‐substituted N ‐pyridylcarbazole derivatives, however, provide only the 1‐acylated products. This method can be applied to a broad scope of substrates. A reaction mechanism has also been proposed. Abstract : We have developed a regioselective pyridyl‐directed C–H acylation reaction of carbazoles that employs aldehydes as the acyl source and provides C‐1 and C‐8 diacylated products in good to high yields. Dihalogenated carbazoles, however, afford 1‐acylated products. A key feature of this strategy includes the use of the easily removable pyridyl‐directing group.